LARANGAN JUAL BELI GHARAR: KAJIAN HADIST EKONOMI TEMATIS BISNIS DI ERA DIGITAL - Nuhbatul Basyariah (Mukaddimah: Jurnal Studi Islam, 2022)
The development of transaction and business models in the current digital era requires Muslims to understand the facts and concepts of correct transactions, in order to avoid acts that violate sharia, one of which is transactions that contain gharar. To understand sharia, we must learn from sources of Islamic law, one of which is the hadith of the Prophet Muhammad. This study aims to describe and analyze comprehensively with various sides of the study of economic hadith about gharar in business. This research is a qualitative type with a literature study approach. The results of the study show that there are many hadiths that explain prohibited buying and selling and business transactions due to the presence of gharar or unclear elements. Because it can harm one of the parties to the transaction. A business is said to be permissible or lawful if it is free from all elements of maghrib; maysir, gharar, usury.